Outcome of transforaminal nerve root block using posterolateral approach in patients with low back ache due to PIVD in a tertiary care centre of North India - Raina, Gagandeep Singh; Gupta, Sanjeev; Kour, Bhavneet; Lone, Zubair A.; Kour, Anita (International Journal of Research in Medical Sciences, 2021)
Background: Back ache has become a common phenomenon in our society, reason being our sedentary and unhealthy lifestyle. Transforaminal administration of steroid and analgesia is an important modality in the conservative management of prolapsed lumbar disc. The aim of this study is to assess functional outcome of transforaminal epidural analgesic injection in cases of chronic back pain due to prolapsed intervertebral disc. Methods: 152 patients who fulfilled the inclusion and exclusion criterias were given the block and were compared pre and post injection using ODI score. Results: Most patients in study were in fourth or fifth decade and had complained of pain for more than a year. L4-L5 was found to be the most common level involved. Post injection 129 patients out of 152 reported minimal pain and most of the patients reported improvement in pain post block. Conclusions: We concluded that tranforaminal block is an effective method of achieving pain relief in most patients for some duration and can help in delaying and in some cases avoiding the need for surgery.